12-4a=-7a+4(-2a-8)

Simple and best practice solution for 12-4a=-7a+4(-2a-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-4a=-7a+4(-2a-8) equation:


Simplifying
12 + -4a = -7a + 4(-2a + -8)

Reorder the terms:
12 + -4a = -7a + 4(-8 + -2a)
12 + -4a = -7a + (-8 * 4 + -2a * 4)
12 + -4a = -7a + (-32 + -8a)

Reorder the terms:
12 + -4a = -32 + -7a + -8a

Combine like terms: -7a + -8a = -15a
12 + -4a = -32 + -15a

Solving
12 + -4a = -32 + -15a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '15a' to each side of the equation.
12 + -4a + 15a = -32 + -15a + 15a

Combine like terms: -4a + 15a = 11a
12 + 11a = -32 + -15a + 15a

Combine like terms: -15a + 15a = 0
12 + 11a = -32 + 0
12 + 11a = -32

Add '-12' to each side of the equation.
12 + -12 + 11a = -32 + -12

Combine like terms: 12 + -12 = 0
0 + 11a = -32 + -12
11a = -32 + -12

Combine like terms: -32 + -12 = -44
11a = -44

Divide each side by '11'.
a = -4

Simplifying
a = -4

See similar equations:

| 23*15=25 | | 3v^2+36v+49-8v=0 | | x-6=24-4x | | 3x^2+x+4=8x | | 6x+4=32-3x | | 3y=5-x | | 1/3(x+12)=12 | | 4(1-2u)=2(u+2) | | 2y=6y-11 | | 6x-4=32-3x | | 43X=8X+1 | | -5x^4+20x^3+60x^2=0 | | 40+3r=-7r+4(8r-1) | | p/1.52=-3,600 | | 2x^2+22x+12=9x+6 | | 3-x-5=7 | | 46+4e=8e+14 | | 32X+3=625 | | -2x+6=4x-6 | | -3w+45=2w | | 0=15+3y | | 13j-100=7j-274 | | x^2+10=3x-3 | | -6b+5+2b=25 | | 5x=15+0 | | 5a-6=-(6-6a)-a | | 5(x+3)=2x-3x | | e/0.76=2,809 | | 3(a-a)+2(a-a)-3(2a-3a)= | | 5x-8=3y | | 6x^2-5=x-4 | | -3(2y+7)=-39 |

Equations solver categories